Identification of Morphological Characteristics of Red Fruit Plants (Pandanus conoideus Lamk.) in Taniwel District, West Seram Regency - H. Makaruku, Marlita; Y. Wattimena, Anna.; J. Lawalata, Imelda (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The red fruit plant (Pandanus conoideus Lamk.) is a plant from the pandan family which is found growing wild in the regions of Papua, Maluku and Papua New Guinea. Red fruit plants contain important nutrients that can be used as a source of degenerative medicine raw materials. The genetic potential of red fruit in natural habitat is not known with certainty. This study aims to identify the morphological characteristics of growing red fruit plants in Taniwel District, West Seram Regency. The research was carried out using field observation and interview methods. Observational data on the morphological characters of the red fruit plants collected were then processed and tabulated. Data is presented in the form of morphological descriptions. The results showed that there were 2 red fruit accessions that were widely cultivated, namely saune ellah and saune oti. The diversity of morphological characteristics of red fruit plants between saune ellah and saune oti, especially in plant height, main stem diameter, branching form, number of branches, fruit length, fruit diameter, leaf length, and leaf width. The number of branches and leaf size are the most determining factors, because red fruit plants with large leaf sizes produce larger fruit sizes compared to accessions with small leaf sizes. Meanwhile, red fruit plants that have a large number of branches will produce more fruit.